The Effect of Using Interactive Animation Media and Syllable Method in Improving the Beginning Reading Ability of Grade 1 Students in Indonesian Language Lessons - Mariana, Ria; Amprasto, Amprasto; Juhana, Juhana (Teknodika, 2024)
This research aims to prove that there is an influence of the use of interactive animation media and the syllable method in improving the initial reading ability of class I students in Indonesian language lessons. The method used in this research is the experimental method, the experimental class and control class were chosen not randomly so that the design in this research is in the form of a Nonequivalent (Pretest and Posttest) Control Group Design. The sample in this research was 153 students. The instrument used in this research was a reading ability test including pretest and posttest, interviews and documentation. Meanwhile, regarding the data that has been obtained from the research results, it is then analyzed and processed statistically using the SPSS version 29.0 for window application, while the data analysis used is a 2-average test analysis and N-gain analysis. The results of the research that has been carried out show that the treatment in the form of learning using interactive animation media and the syllabic method where the average N-Gain score is 0.54  is included in the medium category, so the effectiveness of using interactive animation media and methods syllables are quite effective to be applied in initial reading learning, whereas if we refer to the 4 reading assessment indicators, the results show that the 4 reading indicators include the ability to read letters with an N-Gain value of 0.79 (high), reading syllables with an N-Gain value 0.69 (medium), reading words with an N-Gain value of 0.43 (medium), and reading sentences with an N-Gain value of 0.23 (low).